2009
DOI: 10.1161/strokeaha.108.530352
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolysis in Stroke Mimics

Abstract: Background and Purpose— Intravenous thrombolysis for acute ischemic stroke is usually based on clinical assessment, blood test results, and CT findings. Intravenous thrombolysis of stroke mimics may occur but has not been studied in detail. Methods— We determined frequency, clinical characteristics, and outcome of mimic patients versus patients with stroke treated with intravenous thrombolysis using data of a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
74
2
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(89 citation statements)
references
References 8 publications
8
74
2
5
Order By: Relevance
“…Several studies have reported on the predictors of stroke mimics (Table 4). 10, 14, 15, 16, 17 Most reported that stroke mimics were characterized by low vascular risk factors in young individuals and low NIHSS scores.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported on the predictors of stroke mimics (Table 4). 10, 14, 15, 16, 17 Most reported that stroke mimics were characterized by low vascular risk factors in young individuals and low NIHSS scores.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with aphasia show often low baseline NIHSS scores and the proportion of patients with stroke mimics is higher [12].…”
Section: Discussionmentioning
confidence: 99%
“…Bu nedenle de iskemik inme ön tanısı olan hastalarda, erken dönemde ayırıcı tanı sağlanamıyor ise, IV-tPA uygulamasının getireceği potansiyel yararın önüne geçmemek için, vakit kaybetmeksizin IV-tPA uygulamasının gerçekleştirilmesi önerilmektedir. [6][7][8] Bu bakış açısı ile olgumuz da, endikasyon dahilinde, başağrısı yakınmasının ön planda olmadığı, pür motor afazi kliniği ile IV-tPA uygulamasına aday olmuş, hızla düzelen kliniği itibariyle planlanan tedavi gerçekleştirilmemiştir.…”
Section: Discussionunclassified